Ecological monitoring of landscape technogenic neoplasms - Daria A. Dostovalova; Alexander Z. Glukhov; Nikolay S. Podgorodetsky; Sergey P. Zhukov (RUDN Journal of Ecology and Life Safety, 2024)
Mine rock dumps belong to the category of landscape technogenic neoplasms and represent a complex of anthropogenically transformed natural components. Rock dumps cause some damage to the environment due to the withdrawal of agricultural land from use, emissions of gorenje products, dust particles, flushing of pollutants, soil salinization, erosion of slopes. The main optimal measure to reduce the impact of rock dumps on the environment for Donbass is the biological reclamation of their surface. It is based on mandatory continuous environmental monitoring, which represents a set of observations of the current state and forecasting of further changes in: the state of atmospheric air, surface waters, radiation conditions, soil conditions, flora, fauna and public health in the territory of a landscape technogenic neoplasm and adjacent areas. The use of the principles of environmental monitoring will help to stabilize the landscape technogenic neoplasm as an ecosystem and contribute to the sustainable development of Donbass as an industrial region. The work carried out monitoring of the state of the green spaces of the rock dump sh. 5/6 named after. Dimitrov, located within the city of Donetsk, DPR. An inventory of green spaces and the landscaping object itself was carried out, an assessment of the effectiveness of reclamation measures was carried out, the average degree of disturbance of vegetation cover on the rock dump was determined. The results of studies of the state of the stand of a rock dump using a visual assessment scale are presented. A visual assessment of the following diagnostic signs of OCD was carried out: crown density, the presence of dead branches on the trunk and the degree of damage to the leaves by toxicants, pathogens and insects (the average area of necrosis, chlorosis and overeating).